Bringing Images and Cultural Contents into English Textbooks for Intercultural Classroom - Tiara Damayanti; Yohanes Gatot Sutapa Yuliana; Sudarsono Sudarsono (Jurnal Pendidikan Bahasa, 2023)
English is becoming a foreign language in Indonesia. There are several resources that can be used by the teacher and instructor to facilitate the teaching and learning process in gaining the four main English skills. A textbook is becoming one of the learning resources in formal and informal education. The learners are expected to master the source, target, and international culture during the learning process. This research aims to explain the key terms related to the topic being discussed and to identify the importance of bringing images and cultural content into English textbooks for an intercultural classroom atmosphere. A descriptive qualitative study that utilizes the library research methodology is implemented to gather the data for this research. The findings show that images and cultural contents are the important keys as they can get the students’ interest and attention during the class hour, images can also be the representation of how culture is done, and if the images and cultural contents are combined together it will help the students to get the deeper understanding of imagination about things that they cannot see directly at the classroom.